(untitled) (Historia, 2021)
A ""brotherhood of self sacrifice and service""? Interrelations on commando during the Anglo-Boer War of 1899-1902. During the Anglo-Boer War of1899-l902 the burghers on commando were obliged to be in one another’s company for more than two and a half years. Despite the traditional individuality of the burgher, a strong bond and a feeling of togetherness came into being on commando because of the war conditions. Together they cherished the same ideals of self-preservation and independence. The unit in which this collaboration occurred particularly, was the corporalship which was made up of twelve to eighteen men and which was sometimes divided into two or three sections. Within this corporalship or section the burghers often grouped themselves into twos as so-called buddies. A willingness to share within sections or groups was to many, a way of life. And yet in most cases there was an unwillingness to admit a stranger, who would draw from their resources, into the section. Although only males between sixteen and sixty years of age were liable for military service, there were a number of boys younger than sixteen and men older than sixty on commando. Boys, who were too young to handle a rifle, had to look after the livestock or the horses. The men over sixty had a tough time in the veld. The older burghers often treated the young with a self-sufficient patriarchism, while the latter usually treated the older men with respect. Relations between the Free Staters and Transvalers on commando depended on the situation and were not experienced the same way by all burghers. Those inspired by nationalism regarded themselves from the outset as one nation. Military setbacks like the surrender of General P .A. Cronje were, however, a blow to the good relations. After the British occupation of Pretoria in June 1900 the relationship improved, partly because of the realization amongst the ’bittereinders’ that they were fighting for a common cause.